PD-L1 – inhibitors in neuroendocrine neoplasia: Results from a real-life study. Issue 1 (8th January 2021) - Özdirik, Burcin; Jann, Henning; Bischoff, Philip; Fehrenbach, Uli; Tacke, Frank; Roderburg, Christoph; Wiedenmann, Bertram
Abstract : Abstract: Immune check-point inhibitors (ICIs) have changed our view on how to treat cancer. Despite their approval in treatment of many different cancers, efficacy of immune check-point inhibitors (ICI) in neuroendocrine neoplasia is limited and poorly understood. Established treatment options of neuroendocrine tumors (NET) and neuroendocrine carcinomas (NECs) are based on surgery, tumor-targeted medical treatments, Peptide Receptor Radionuclide Therapy (PRRT), and locoregional therapies. However, in many patients these treatments lose efficacy over time, and novel therapies are urgently needed. We report on 8 patients diagnosed with neuroendocrine neoplasms (NEN) that were treated with ICI (pembrolizumab, avelumab, nivolumab plus ipilimumab) as salvage therapy. In this cohort, we observed tumor response with partial remission in 3 patients and stable disease in 1 patient. Four patients showed progressive disease. Of note, responses were observed both in PD-L1 positive and PD-L1 negative patients. Here, we discuss clinical courses of these patients in the context of available literature to highlight limitations and drawbacks currently preventing the use of ICI in routine management of patients with NEN. Abstract : Supplemental Digital Content is available in the text